Subdural arachnoidal cyst of the spinal cord: etiology, clinical presentation, surgical strategy and results - Fonseca, Joelton; Lynch, José Carlos; Policarpo, Fabiana; Esteves, Celestino; Bomfim, Cleber; Welling, Leonardo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2012)
Objective: Of this study is identifying the clinical manifestations, discuss the etiology, and present the surgical treatment nuances and outcomes of patients with sub dural arachnoidal cysts (AC). Method: A retrospective study was carried out with 7 consecutives patients with spinal cord subdural AC, diagnosed, evaluated and operated at the Neurosurgical department of Servidores do Estado Hospital, from 1996 to 2010. The radiological studies, patient records, surgical descriptions and surgical videos, were reviewed, creating a database from which information was collected. The follow-up varied from 2 to 168 months (mean, 48 months). All cysts were histopathological verified. Results: Five AC were located on the thoracic spinal cord, one were located anterior in the cervical region, and one at the lumbar spinal level. The complete resection of the cyst was performed in 4 surgeries. Three patients had cysts located ventral to the cord, which precluded complete excision. The symptoms in four patients demonstrated major improvement. There was no operative death in this series, there was no major complications related to surgery. Conclusion: AC should be considered in the differential diagnosis of lesions causing myelopathy and/or a radicular pain syndrome. Microsurgical resection or generous fenestration in cysts effectively ameliorated patients’ symptomatology.
Keywords: Arachnoid cysts; spinal cord compression; sciatica; myelitis; microsurgery